Study of Two Ships Approaching Process and Towing Motion under Wave Action - Shengtao Chen; Han Zou; Guocai Qi; Dongju Li; Zhouyuan Xu (Journal of Marine Science and Engineering, 2022)
The rescue of ships in distress at sea relies mainly on rescue vessels, which includes the approaching process and the towing motion of the two ships. Ship rescue can be reduced to a two-ship problem, primarily involving the relative motion between ships during rescue. We established a mathematical model of ship motion based on the viscous fluid N-S equation, and the approaching process of two Wigley ships under waves was simulated in a two-dimensional plane. Then, according to three-dimensional potential flow theory, the coupled motion response model of the ships under six degrees of freedom was constructed, and calculation models of wind, waves, currents and other environmental disturbance factors were established to numerically calculate the towing motion. The results show that the upstream vessel has a lower heave motion amplitude and higher roll motion amplitude during the approaching process; A ratio of 1.5 times the width of the ship is the critical area where the motion of the two ships interacts with each other; For the berthing process, the faster the motion of the active vessel is, the lower the motion amplitude will be for both upstream and downstream vessels. When towing under rough sea conditions, changes in wave height and towing velocity have a large influence on the coupling effect of the towing system. When towing, head-on waves and low sea conditions are preferred, and the velocity should be sufficiently high to reduce the influence of cable self-weight on the towed ship. According to the simulations, the recommended velocity range is 3–5 m/s. Finally, a ship model scaling model was developed based on the similar quasi-Froude number of the ship model test, and the simulation results were verified by conducting parallel and towing tests of the model in a basin with a spherical wave-maker device.